Health Law Reform in Ensuring Physician Competency Based on the Integration of Ethics, Discipline and Science for Global Welfare - Rika Noviantini; Faisal Santiago (Greenation International Journal of Law and Social Sciences, 2025)
Doctors are a fundamental aspect in ensuring the quality of health services, as well as being an integral part of the protection of the right to health as guaranteed in the constitution and international human rights instruments. However, medical practice still faces various challenges, ranging from disparities in the quality of medical education, weak competency test mechanisms, to the lack of optimal integration of professional ethics, discipline, and science in the health legal system. This condition poses a risk to patient safety and reduces public trust in medical services. This research aims to analyze the need for health law reform in ensuring the competence of doctors, as well as formulate an integration model between ethics, discipline, and science as the main pillars of equitable and well-being oriented medical professional governance. The method used is normative legal research with legislative, conceptual, and comparative approaches. Primary and secondary legal data are analyzed qualitatively through the study of doctrines, norms, and practices of the governance of the medical profession in various countries. Health law reform needs to be directed at strengthening regulations on physician competency standards, transparent certification and recertification mechanisms, and professional supervision systems that are integrated between ethics, discipline, and law. The integration model can be an instrument to ensure that every doctor has measurable competence, maintained professional ethics, and clear legal responsibilities in healthcare practice. Ensuring the competence of doctors through health law reform based on the integration of ethics, discipline, and science is a strategic step to improve the quality of medical services, strengthen patient protection, and realize global justice and welfare.